Venous thrombosis in von Willebrand disease as observed in one centre and as reported in the literature. Issue 1 (January 2015) - Girolami, Antonio; Tasinato, Valentina; Sambado, Luisa; Peroni, Edoardo; Casonato, Allesandra
<x xml:space="preserve">Abstract</x> The aim of this article was to investigate the prevalence of venous thrombosis in patients with von Willebrand disease. Personal records on 486 patients were reevaluated together with a time unlimited PubMed search. The venous thrombotic event had to be proven by objective means. Only cases of congenital von Willebrand disease were taken into consideration and all types of the diseases were included. No case of venous thrombosis was reported in our cohort of patients. On the contrary, 33 patients with proven venous thrombosis were gathered from the literature (17 cases of deep venous thrombosis with or without pulmonary embolism; isolated pulmonary embolism was seen in seven instances, superficial veins or portal system thrombosis was present in the remaining cases). Associated risk factors, mainly replacement therapy, were present in 26 cases. Therapeutic approach was usually based on heparin and Coumadin. Overall results were fair or good, as no fatalities occurred.